Development of a screener to assess athlete risk behavior of not using third-party tested nutritional supplements - Wardenaar, Floris C.; Schott, Kinta D.; Seltzer, Ryan G. N.; Gardner, Christopher D. (Frontiers in Nutrition, 2024)
The aim of this cross-sectional study was to develop a questionnaire-based algorithm to predict athletes use of third-party tested (TPT) supplements. Therefore, a nutritional supplement questionnaire was used with a section about self-reported TPT supplement use. Outcomes were randomly assigned to a training dataset to identify predictors using logistic regression models, or a cross-validation dataset. The training data were used to develop an algorithm with a score from 0-100 predicting use or non-use of TPT nutritional supplements. A total of n=410 NCAA Division I student-athletes (age: 21.4±1.6 years, 53% female, from >20 sports) were included.Then n=320 were randomly selected, of which 34% (n=109) of users consistently reported that all supplements they used were TPT. Analyses resulted in a 10-item algorithm associated with use or non-use of TPT. Risk quadrants provided the best fit for classifying low vs. high risk toward inconsistent TPT-use resulting in a cut-off ≥60% (χ2(4)=61.26, P<0.001), with reasonable AUC 0.78. There was a significant association for TPT use (yes/no) and risk behavior (low vs. high) defined from the algorithm (χ2(1)=58.6, P<0.001). The algorithm had a high sensitivity, classifying 89% of non-TPT users correctly, while having a low specificity, classifying 49% of TPT-users correctly. This was confirmed by cross-validation (n=34), reporting a high sensitivity (83%), despite a lower AUC (0.61). In conclusion, the algorithm classifies high-risk inconsistent TPT-users with reasonable accuracy, but lacks the specificity to classify consistent users at low risk. This approach should be useful in identifying athletes that would benefit from additional counseling.